Critical Study of PP No. 56 of 2021 Concerning Royalty Payments for Live Performances of Singers Who Reperform Songs from Other Musicians at Cafes in Cirebon Regency - Muzakki, Muhammad Naufal Hammam; Pratama , Adhitya Yudha; Krisnandar , Iis; Solichin , Solichin (Journal of Legal and Cultural Analytics, 2025)
This study examines the implementation of Government Regulation Number 56 of 2021 concerning the Management of Song and/or Music Copyright Royalties, especially in live performances by cover singers in Cirebon Regency cafes. This study is based on the increasing use of music in commercial activities in public spaces that require the payment of royalties to copyright holders. Methods, The normative juridical method analyzes legal regulations and field data from interviews with related agencies, business actors, singers, local musicians, and LMKs such as WAMI. The results show that implementing this regulation is not optimal due to the lack of understanding of business actors, the absence of derivative rules in the regions, and the lack of socialization from the government and LMKN. Many cafes do not consider music performances commercial activities requiring royalties. Meanwhile, local musicians tend to be permissive towards the use of their songs. This study recommends collaboration between local governments, LMKN, and business actors to develop technical rules, expand socialization, and establish appropriate tariff schemes so that copyright protection runs fairly without burdening small business actors.